Peran Artificial Intelligence (AI) dalam Meningkatkan Kemampuan Berpikir Kritis Siswa - Fahmy Syahputra; Elsa Sabrina; Alvin Evraim Situmorang; Marchell Gabriel Manurung; Safira Nazwa Putri; Sarwedi Parhehean Tua (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study aims to analyze the contribution of artificial intelligence (AI) use in supporting students’ critical thinking skills across the cognitive levels of Bloom’s taxonomy. A descriptive quantitative survey design was employed. Data were collected using a 20-item questionnaire administered via Google Forms to 45 students. Descriptive analysis was conducted by summarizing and reporting the proportion of responses for each Bloom level (remembering, understanding, applying, analyzing, evaluating). The results show that the highest proportion occurs at the understanding level (26.7%), followed by analyzing (22.2%), evaluating (20.0%), applying (17.8%), and remembering (13.3%). These findings indicate that students tend to use AI more to comprehend learning materials and break down information than merely to recall facts. The study concludes that AI can function as a learning partner that supports critical thinking processes—particularly at the understanding and analyzing levels—provided that its use is guided pedagogically to align with instructional goals.